Titanium material with gradient nano-twin crystals and preparation method thereof

By annealing, grinding, low-temperature laser impact strengthening and tempering treatment on titanium materials, a longitudinal gradient nanoscale twin network is formed, which solves the problem of insufficient strength and fatigue life of titanium materials in the prior art, and achieves the effect of significantly improving strength and fatigue life, while improving processing adaptability.

CN119876808APending Publication Date: 2025-04-25SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510087124.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art has limitations in improving the strength and fatigue life of titanium materials, especially in maintaining ductility while increasing strength. The process requirements for low-temperature forging and DC electrodeposition are high and the applicability is low.

Method used

By annealing, polishing, and multi-pass laser impact enhancement treatment under a low temperature environment of 77K-90K, and finally tempering treatment is carried out to form a longitudinal gradient nanoscale twin network from the surface to the core.

Benefits of technology

It significantly improves the strength and fatigue life of titanium materials, while improving processing adaptability and controllability, avoiding limitations on complex geometric shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876808A_ABST
    Figure CN119876808A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium material with gradient nano twin crystals and a preparation method of the titanium material, and relates to the technical field of titanium materials. A titanium base material is subjected to annealing treatment, grinding and polishing, then multi-pass laser shock peening treatment is carried out in a low-temperature environment, and finally tempering treatment is carried out. By the adoption of the preparation method, the longitudinal gradient nanoscale twin network from the surface to the core can be obtained in Ti, the obdurability of the twin network is remarkably improved, the anti-fatigue life of the twin network is remarkably prolonged, the method is not limited by complex geometrical shapes, and higher machining adaptability and controllability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium materials, and in particular to a titanium material with gradient nano twins and a preparation method thereof. Background Art

[0002] Titanium has the highest specific strength among metallic elements, as well as excellent corrosion resistance. However, pure titanium has moderate strength, and one way to harden titanium industrially is to alloy it with other elements such as oxygen (O), aluminum (Al), and vanadium (V) to form a solid solution or dual-phase structure. The strength of these alloys is improved, but always at the expense of ductility. In addition to this, the introduction of nano twin networks can also improve the properties of metal alloys. Because twin boundaries are low-energy grain boundaries, this property makes them more stable than random high-angle grain boundaries. Therefore, twinning can greatly increase strength without sacrificing fracture resistance. Reducing the grain size to the submicron and nanometer range leads to a significant increase in yield strength.

[0003] The prior art uses a direct current electrodeposition method to prepare a bulk high-purity copper plate with nano-scale growth twins, and exhibits high strength. In the close-packed hexagonal structure, it is also found that nano-twinned titanium can be generated under low-temperature forging, which has ultra-high strength and ductility. However, the strengthening effect of direct current electrodeposition is usually concentrated on the surface or shallower areas, and the coating of the direct current electrodeposition layer is usually thin, which has limited effect on improving fatigue life. The processing temperature of low-temperature forging needs to be controlled within a specific range, and proper cooling treatment is required, and the environmental requirements are relatively high. Low-temperature forging and direct current electrodeposition have low applicability to factors such as materials, workpiece shape and size during the strengthening process.

[0004] In addition, the existing methods for producing titanium twins can only produce high-density deformation twins, and cannot significantly improve the toughness and fatigue life of titanium. Summary of the invention

[0005] The purpose of the present invention is to provide a titanium material with gradient nano twins and a preparation method thereof, aiming to significantly improve the strength, toughness and fatigue life of titanium.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a method for preparing a titanium material having gradient nanotwins, comprising:

[0008] The titanium substrate is subjected to annealing treatment, grinding and polishing in sequence to obtain a pretreated substrate;

[0009] The pretreated substrate is subjected to multiple laser shock peening treatments in a low temperature environment of 77K-90K, and then subjected to tempering treatment.

[0010] In an optional embodiment, during each laser shock peening process, the laser wavelength is controlled to be 1064nm, the pulse duration is 8ns-15ns, the overlap rate is 50%-80%, and the pulse energy density is 2GW / cm 2 -18GW / cm 2 .

[0011] In an optional embodiment, during each laser shock peening process, the laser wavelength is controlled to be 1064nm, the pulse duration is 8ns-12ns, the overlap rate is 50%-60%, and the pulse energy density is 3.0GW / cm 2 -6.0GW / cm 2 .

[0012] In an optional embodiment, during each laser shock peening process, the aluminum foil is used as a sacrificial layer, and a constraining layer is provided on the aluminum foil;

[0013] Preferably, the number of laser shock peening treatments is 2-6 times;

[0014] Preferably, the aluminum foil is replaced before each laser shock peening treatment.

[0015] In an optional embodiment, the constraining layer is tempered glass with a thickness of 4 mm to 6 mm.

[0016] In an optional embodiment, multiple laser shock peenings are performed using a zigzag laser path, with the laser beam kept perpendicular to the sample surface.

[0017] In an optional embodiment, the pre-treated substrate is placed in liquid nitrogen, and the surface of the liquid nitrogen is lower than the surface of the pre-treated substrate to form a low temperature environment.

[0018] In an optional embodiment, during the tempering treatment, the treatment temperature is controlled to be 100° C.-200° C., and the treatment time is 2 h-10 h.

[0019] In an optional embodiment, the annealing treatment is performed under an inert atmosphere, the annealing temperature is controlled to be 750° C.-850° C., and the annealing time is 2 h-5 h.

[0020] In a second aspect, the present invention provides a titanium material with gradient nanotwins, which is prepared by the preparation method of any one of the aforementioned embodiments.

[0021] The present invention has the following beneficial effects: the titanium substrate is annealed, polished, and then subjected to multiple laser shock strengthening treatments in a low temperature environment, and finally subjected to tempering treatment. The preparation method of the present invention can obtain a longitudinal gradient nano-scale twin network from the surface to the core in Ti, significantly improving its toughness and fatigue life, and this method is not limited by complex geometric shapes and has stronger processing adaptability and controllability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 Provide a working process diagram of the preparation method of the present invention;

[0024] Figure 2 Provide a schematic diagram of the preparation method of the present invention;

[0025] Figure 3 This is the gradient twin structure diagram obtained by three low-temperature laser shock strengthening;

[0026] Figure 4 This is the TEM image of the nano twin structure near the impact surface after three low-temperature laser shock strengthening;

[0027] Figure 5 This is the hardness distribution diagram along the shock wave propagation direction after three low-temperature laser shock strengthening;

[0028] Figure 6 This is the gradient twin structure diagram obtained by 5 low-temperature laser shock strengthening;

[0029] Figure 7 This is the gradient twin structure diagram obtained by one low-temperature laser shock strengthening. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0031] Laser shock peening (LSP) has good controllability and can flexibly adjust the strengthening effect by adjusting the laser parameters. It is applicable to complex shapes and large-sized workpieces and has stronger adaptability. LSP uses ultra-high power density (GW / cm 2 ), ultrashort pulses (ns) and high-pressure plasma, the laser irradiates the absorption layer covering the surface of the material, causing it to vaporize and ionize to produce high-pressure plasma. The explosive expansion of the plasma produces a high-pressure shock wave (GPa level), which impacts and penetrates the surface of the material. When the peak pressure of the shock wave is higher than the yield strength of the material, it will induce an ultra-high strain rate (>10 6 / s), thus forming a microstructure change layer and a compressive residual stress layer with a certain depth. The significant modification effect brought by LSP has brought the strengthening effect of the metal surface to a new level.

[0032] The present invention creatively applies laser shock strengthening (LSP) processing technology to the treatment of titanium substrates, controls the pretreatment process and the operating conditions of the LSP treatment, and performs LSP treatment under low temperature conditions to obtain a longitudinal gradient nanoscale twin network from the surface to the core in Ti. The present invention demonstrates an efficient and practical strengthening approach that can achieve significant improvements in toughness and fatigue life in Ti without involving special and usually expensive alloying elements.

[0033] The embodiment of the present invention provides a method for preparing a titanium material having gradient nano-twins, the steps of which are as follows:

[0034] S1. Preprocessing

[0035] The titanium substrate is subjected to annealing treatment and grinding and polishing in sequence to obtain a pre-treated substrate. Annealing treatment can obtain an equiaxed structure and eliminate stress, and grinding and polishing can significantly reduce the surface roughness, thereby improving the effect of laser shock peening treatment by affecting the propagation of shock waves.

[0036] In some embodiments, the annealing treatment is performed in an inert atmosphere, the annealing temperature is controlled to be 750° C.-850° C., and the annealing time is 2 h-5 h. By regulating the temperature and time of the annealing treatment, stress can be better eliminated and an equiaxed structure can be obtained.

[0037] Specifically, the annealing treatment can be performed in a vacuum furnace, and the annealing temperature can be 750° C., 780° C., 800° C., 830° C., 850° C., etc.; the annealing time can be 2 h, 3 h, 4 h, 5 h, etc. The type of inert atmosphere is not limited, and it can be argon, nitrogen, etc.

[0038] In some embodiments, grinding and polishing can be performed using 400# to 2000# sandpaper, and the roughness after grinding and polishing is controlled to reach Ra 1.

[0039] S2. Laser shock peening treatment

[0040] like Figure 1 and Figure 2 As shown, the pretreated substrate is subjected to multi-pass laser shock peening treatment in a low temperature environment of 77K-90K. By performing multi-pass laser shock peening treatment in a low temperature environment, the number of twins can be increased, and a longitudinal gradient nano-scale twin network from the surface to the core can be generated, which significantly improves its strength, toughness and fatigue life.

[0041] Specifically, the temperature of the low temperature environment can be 77K, 80K, 85K, 90K, etc. The method of forming the low temperature environment is not limited, and can be as follows: Figure 2 Liquid nitrogen is used to form a low-temperature environment. The pretreated substrate is placed in liquid nitrogen, and the surface of the liquid nitrogen is made lower than the surface of the pretreated substrate to form a low-temperature environment. In the actual operation process, the sample fixture is placed in a foam box with a liquid nitrogen environment. In order to control the temperature to 77K-90K, liquid nitrogen is continuously added to the foam box so that the surface of the liquid nitrogen is slightly lower than the surface of the sample, and the heat is transferred to the sample. After a period of time, the heat loss and heat replenishment of the sample gradually tend to balance, and the LSP experiment is immediately carried out in the low-temperature treatment. Low-temperature deformation can increase the stored energy (in the form of defects, such as dislocations) by suppressing dynamic recovery, thereby further strengthening the material. In addition to producing more defects, plastic deformation at low temperatures can also produce high-density deformation twins, which have good thermal stability.

[0042] In actual operation, a pulse laser can be used to emit pulsed laser, and a mechanical arm can be used to move the pre-processed substrate so that the laser point covers the entire substrate surface. Since one laser point is emitted each time, a zigzag laser path can be used to make the laser point completely cover the substrate surface. During the process, the laser beam remains perpendicular to the sample surface. Figure 1 As shown, there are some overlapping parts of the laser points, and the ratio of the area of ​​the overlapping parts to the total area is the overlapping rate.

[0043] In some embodiments, during each laser shock peening process, the laser wavelength is controlled to be 1064nm, the pulse duration is 8ns-15ns, the overlap rate is 50%-80%, and the pulse energy density is 2GW / cm 2 -18GW / cm 2 In a preferred embodiment, during each laser shock peening process, the laser wavelength is controlled to be 1064nm, the pulse duration is 8ns-12ns, the overlap rate is 50%-60%, and the pulse energy density is 3.0GW / cm 2 -6.0GW / cm 2By adjusting parameters such as wavelength, pulse duration, overlap rate, and pulse energy density, the number and distribution of twins can be increased, and the toughness and fatigue life of the product can be improved.

[0044] The pulse duration can be 8ns, 9ns, 10ns, 11ns, 12ns, 13ns, 14ns, 15ns, etc. The short pulse width can quickly concentrate a large amount of laser energy on the surface of the material to generate a high-pressure plasma shock wave. The larger shock wave intensity can produce high-amplitude residual compressive stress on the surface of the material, which helps to significantly improve the surface strength and hardness. However, due to the short pulse time, the penetration depth of the shock wave inside the material is relatively small, and the compressive stress layer is thin. When the pulse width increases, the influence depth of the residual compressive stress increases, and the compressive stress layer becomes thicker, which is suitable for scenarios where deep structure strengthening is required, such as fatigue resistance enhancement.

[0045] Specifically, the overlap rate may be 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc. A high overlap rate may form a more uniform residual compressive stress distribution, while a too high overlap rate may cause excessive deformation in the repeated impact area, or even surface damage or ablation.

[0046] Specifically, the pulse energy density can be 2GW / cm 2 、3GW / cm 2 , 5GW / cm 2 , 6GW / cm 2 , 8GW / cm 2 、10GW / cm 2 、13GW / cm 2 、15GW / cm 2 、18GW / cm 2 When the pulse energy density is high, the shock wave is stronger and can penetrate deeper into the material more effectively. Too high a pulse energy density can easily cause local overheating of the material surface, leading to enhanced thermal effects, which may cause microcracks, melting or other damage. Especially when multiple impacts are performed, the surface temperature rise will be more obvious.

[0047] In some embodiments, during each laser shock peening process, aluminum foil is used as a sacrificial layer, and a constraining layer is provided on the aluminum foil, and the constraining layer can be a tempered glass with a thickness of 4 mm to 6 mm, but is not limited thereto. The aluminum foil is used as a sacrificial layer, and a layer of tempered glass is added on the aluminum foil as a constraining layer to increase the peak pressure of the laser shock wave.

[0048] Furthermore, the aluminum foil is replaced before each laser shock peening process. The main purposes of replacing the aluminum foil are: (1) to ensure the efficiency of plasma generation: after a shock, the aluminum foil is often damaged by high temperature and high pressure and becomes unsuitable for absorbing laser energy. If it is not replaced, the efficiency of plasma generation will be reduced, affecting the effect of shock peening. (2) to maintain a uniform shock effect: a complete and uniform aluminum foil layer needs to be replaced for each shock to ensure consistent strengthening effects in each pass. If it is not replaced, the damaged aluminum foil will cause uneven laser absorption in different areas, affecting the processing quality. (3) to avoid surface residue effects: the old aluminum foil may leave ablation products or contaminants on the surface of the workpiece, affecting the laser absorption and shock effect of the next pass. Replacing the aluminum foil can ensure surface cleanliness and ensure the strengthening effect of each pass.

[0049] In some embodiments, the laser shock peening treatment is performed 2-6 times, such as 2 times, 3 times, 4 times, 5 times, 6 times, etc. That is, the laser shock peening treatment can be repeated 1-5 times. The relationship between the laser energy density and the number of shocks is considered comprehensively: if the number of shocks is too small or the laser energy density is too low, the gradient twin structure is not obvious; if the number of shocks is too large or the laser energy density is too high, cladding will occur on the surface, which is not conducive to the improvement of mechanical properties.

[0050] S3. Tempering

[0051] Tempering after step S2 can relieve unwanted residual stresses without inducing additional grain coarsening, while achieving a longitudinally gradient nanoscale twin network, significantly improving tensile strength and fatigue life.

[0052] In some embodiments, during the tempering process, the treatment temperature is controlled to be 100°C-200°C, and the treatment time is 2h-10h. By adjusting the treatment temperature and time of the tempering treatment, the unwanted residual stress can be better eliminated and the longitudinal gradient nano-scale twin network can be better formed. Specifically, the treatment temperature can be 100°C, 130°C, 150°C, 180°C, 200°C, etc.; the treatment time can be 2h, 4h, 6h, 8h, 10h, etc.

[0053] An embodiment of the present invention also provides a titanium material with gradient nanotwins, which is prepared by the above-mentioned preparation method provided by an embodiment of the present invention, and has a longitudinal gradient nanoscale twin network from the surface to the core, which can significantly improve its strength, toughness and fatigue resistance life.

[0054] It should be noted that from the perspective of action depth, laser shock peening (LSP) uses ultra-high power density (GW / cm 2 ), ultrashort pulses (nanoseconds) and high-pressure plasmas can induce ultrahigh strain rates (>10 6 / s), thus forming a microstructure change layer with a certain depth (~2000μm) on the surface of pure titanium, such as gradient nanotwin structure and gradient FCC phase. From the perspective of organizational characteristics, low temperature treatment inhibits the dynamic recovery and annihilation of dislocation structure induced by laser shock wave, resulting in a higher dislocation density. In addition, low temperature can also inhibit the movement and slip of dislocation structure, which is more conducive to the formation of mechanical twins.

[0055] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0056] Example 1

[0057] This embodiment provides a method for preparing a titanium material with gradient nano-twins, and the steps are as follows:

[0058] (1) Sample pretreatment

[0059] Before LSP, the hot-rolled pure titanium (3 mm thick, the same below) was placed in a vacuum furnace filled with argon and annealed at 800 ° C for 3 hours to obtain an equiaxed structure and eliminate stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0060] (2) LSP processing

[0061] Place the sample fixture in a foam box with liquid nitrogen. Continuously add liquid nitrogen to the foam box so that the liquid nitrogen surface is slightly lower than the sample surface, and transfer heat to the sample to control the temperature at 77 K. After a period of time, when the heat loss and heat supplement of the sample gradually tend to balance, the LSP experiment is immediately carried out in the low temperature treatment.

[0062] The wavelength is 1064nm and the pulse laser energy is 3.98GW / cm 2 , the pulse duration is 8ns, and the overlap rate is 50%. Aluminum foil is used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2mm is added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. Multiple LSPs are performed using a zigzag laser path, and the laser beam is always kept perpendicular to the sample surface.

[0063] The laser beam was parallel to the ND (normal direction) of the annealed pure titanium, that is, perpendicular to the RD (rolling direction)-TD (transverse direction) surface with an area of ​​2cm×2cm, and the laser shock strengthening was repeated 3 times at the same location. The aluminum foil needed to be replaced each time until the end of the experiment.

[0064] (3) Tempering

[0065] The material after low-temperature LSP was heat treated (tempered) at a temperature of 100° C. for 3 hours, and then the sample was taken out of the vacuum heat treatment furnace and air-cooled to room temperature.

[0066] After treatment, the laser-strengthened area was cut in half along the ND direction and the RD direction, and the ND-RD surface was polished and etched to obtain a gradient twin structure as shown in Fig. Figure 3 As shown. Figure 3 It can be seen that the twins are small in size and present a needle-like morphology. There are a large number of twins close to the surface of pure titanium, and the twins cross each other to form a network structure. Along the direction of shock wave propagation (>400μm), the number of twins gradually decreases, and the twins are parallel to each other. Far away from the surface, very few twins exist in some grains. As the shock wave propagates, the number of twins gradually decreases, and the twins change from crossing each other to being parallel to each other and then to a single twin, showing an obvious gradient twin structure. Further TEM analysis was performed on some grains close to the surface of pure titanium, as shown Figure 4 As shown in the figure, it can be found that there are a large number of intersecting twins in the grains after laser shock, and the size of the twins is small, about 200nm, and they are all nano twins.

[0067] The mechanical properties of pure titanium after laser shock strengthening were tested, such as Figure 5 As shown in the figure, the maximum microhardness of the upper surface after three low-temperature LSP treatments reached 146.8HV, which was 41% higher than that of the untreated sample (104HV). It can be seen that the LSP treatment significantly improved the microhardness of pure Ti. As the depth increases, the microhardness of the LSP-treated sample gradually decreases due to the gradual decrease in the number of nanotwins. For the three LSP samples, at a depth of 2000μm, the microhardness drops to a value close to that of the untreated sample. Therefore, after three LSP treatments, the hardened layer can reach 2000μm.

[0068] The fatigue life of the samples was tested. Under the same stress amplitude (75MPa), the fatigue life of the three LSP treatments was significantly increased to 148691 times. Compared with the 96286 fatigue life of the original pure Ti, the fatigue life was increased by 54%.

[0069] Example 2

[0070] This embodiment provides a method for preparing a titanium material with gradient nano-twins, and the steps are as follows:

[0071] (1) Sample pretreatment

[0072] Before LSP, the hot-rolled pure titanium was placed in a vacuum furnace filled with argon and annealed at 800°C for 3 hours to obtain an equiaxed structure and relieve stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0073] (2) LSP processing

[0074] Place the sample fixture in a foam box with liquid nitrogen. Continuously add liquid nitrogen to the foam box so that the liquid nitrogen surface is slightly lower than the sample surface, and transfer heat to the sample to control the temperature at 77 K. After a period of time, when the heat loss and heat supplement of the sample gradually tend to balance, the LSP experiment is immediately carried out in the low temperature treatment.

[0075] The wavelength is 1064nm and the pulse laser energy is 3.98GW / cm 2 , the pulse duration is 8ns, and the overlap rate is 50%. Aluminum foil is used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2mm is added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. Multiple LSPs are performed using a zigzag laser path, and the laser beam is always kept perpendicular to the sample surface.

[0076] The laser beam was parallel to the ND (normal direction) of the annealed pure titanium, that is, perpendicular to the RD (rolling direction)-TD (transverse direction) surface with an area of ​​2cm×2cm, and laser shock strengthening was performed 5 times. The aluminum foil needed to be replaced each time until the end of the experiment.

[0077] (3) Tempering

[0078] The material after low-temperature LSP was heat treated (tempered) at a temperature of 120° C. for 3 hours, and then the sample was taken out of the vacuum heat treatment furnace and air-cooled to room temperature.

[0079] After treatment, the laser-strengthened area was cut in half along the ND direction and the RD direction, and the ND-RD surface was polished and etched to obtain a gradient twin structure as shown in Fig. Figure 6 As shown. Figure 6 It can be seen that the twins are small in size and present a needle-like morphology. There are more twins near the surface of pure titanium, and the twins intersect with each other, filling the entire grain. Along the direction of shock wave propagation, the number of twins gradually decreases, and the area where the twins intersect with each other reaches 700μm. Far away from the surface (1000μm), very few twins exist in some grains. As the shock wave propagates, the number of twins gradually decreases, and the degree of intersecting twins decreases.

[0080] Compared with Example 1, the number of impacts is increased, and the area where the twins intersect each other is wider. The maximum microhardness of the upper surface of the 5-time low-temperature LSP reaches 153.6HV, which is 47% higher than that of the untreated sample (104HV). Under the same stress amplitude (75MPa), the fatigue life of the 5-time low-temperature LSP treatment is significantly improved to 168529 times. Compared with the 96286 fatigue life of the original pure Ti, the fatigue life is increased by 75%.

[0081] Example 3

[0082] (1) Sample pretreatment

[0083] Before LSP, the hot-rolled pure titanium (3 mm thick, the same below) was placed in a vacuum furnace filled with argon and annealed at 800 ° C for 3 hours to obtain an equiaxed structure and eliminate stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0084] (2) LSP processing

[0085] Place the sample fixture in a foam box with liquid nitrogen. Continuously add liquid nitrogen to the foam box so that the liquid nitrogen surface is slightly lower than the sample surface, and transfer heat to the sample to control the temperature at 77 K. After a period of time, when the heat loss and heat supplement of the sample gradually tend to balance, the LSP experiment is immediately carried out in the low temperature treatment.

[0086] The wavelength was selected to be 1064nm and the pulse laser energy was 5.98GW / cm 2 , the pulse duration is 8ns, and the overlap rate is 50%. Aluminum foil is used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2mm is added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. Multiple LSPs are performed using a zigzag laser path, and the laser beam is always kept perpendicular to the sample surface.

[0087] The laser beam was parallel to the ND (normal direction) of the annealed pure titanium, that is, perpendicular to the RD (rolling direction)-TD (transverse direction) surface with an area of ​​2cm×2cm, and the laser shock strengthening was repeated 3 times at the same location. The aluminum foil needed to be replaced each time until the end of the experiment.

[0088] (3) Tempering

[0089] The material after low-temperature LSP was heat treated (tempered) at a temperature of 100° C. for 3 hours, and then the sample was taken out of the vacuum heat treatment furnace and air-cooled to room temperature.

[0090] The results show that increasing the laser shock energy can enhance the effect of LSP on the mechanical properties of pure titanium. The mechanical properties of pure titanium after laser shock strengthening were tested, and the maximum microhardness of the upper surface at the LSP with higher energy three times reached 147.5HV. The fatigue life of the sample was tested, and under the same stress amplitude (75MPa), the fatigue life of the LSP treatment with higher energy three times was significantly improved, reaching 148571 times.

[0091] Example 4

[0092] (1) Sample pretreatment

[0093] Before LSP, the hot-rolled pure titanium (3 mm thick, the same below) was placed in a vacuum furnace filled with argon and annealed at 800 ° C for 3 hours to obtain an equiaxed structure and eliminate stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0094] (2) LSP processing

[0095] Place the sample fixture in a foam box with liquid nitrogen. Continuously add liquid nitrogen to the foam box so that the liquid nitrogen surface is slightly lower than the sample surface, and transfer heat to the sample to control the temperature at 77 K. After a period of time, when the heat loss and heat supplement of the sample gradually tend to balance, the LSP experiment is immediately carried out in the low temperature treatment.

[0096] The wavelength was selected to be 1064nm and the pulse laser energy was 5.98GW / cm 2 , the pulse duration is 10ns, and the overlap rate is 50%. Aluminum foil is used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2mm is added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. Multiple LSPs are performed using a zigzag laser path, and the laser beam is always kept perpendicular to the sample surface.

[0097] The laser beam was parallel to the ND (normal direction) of the annealed pure titanium, that is, perpendicular to the RD (rolling direction)-TD (transverse direction) surface with an area of ​​2cm×2cm, and the laser shock strengthening was repeated 3 times at the same location. The aluminum foil needed to be replaced each time until the end of the experiment.

[0098] (3) Tempering

[0099] The material after low-temperature LSP was heat treated (tempered) at a temperature of 100° C. for 3 hours, and then the sample was taken out of the vacuum heat treatment furnace and air-cooled to room temperature.

[0100] The results show that increasing the pulse time has no significant effect on improving the mechanical properties of pure titanium. The mechanical properties of pure titanium after laser shock strengthening were tested, and the maximum microhardness of the upper surface at the LSP with three longer pulse times reached 152.4HV. The fatigue life of the sample was tested, and under the same stress amplitude (75MPa), the fatigue life of the three higher energy LSP treatments was slightly increased to 149565 times.

[0101] Comparative Example 1

[0102] The main difference between this comparative example and Example 1 is that the number of laser impact operations is reduced, and the specific steps are as follows:

[0103] (1) Sample pretreatment

[0104] Before LSP, the hot-rolled pure titanium was placed in a vacuum furnace filled with argon and annealed at 800°C for 3 hours to obtain an equiaxed structure and relieve stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0105] (2) LSP processing

[0106] Place the sample fixture in a foam box with liquid nitrogen. Continuously add liquid nitrogen to the foam box so that the liquid nitrogen surface is slightly lower than the sample surface, and transfer heat to the sample to control the temperature at 77 K. After a period of time, when the heat loss and heat supplement of the sample gradually tend to balance, the LSP experiment is immediately carried out in the low temperature treatment.

[0107] The wavelength is 1064nm and the pulse laser energy is 3.98GW / cm 2 , the pulse duration is 8ns, and the overlap rate is 50%. Aluminum foil is used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2mm is added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. A zigzag laser path is used for 1 LSP, and the laser beam is always kept perpendicular to the sample surface.

[0108] (3) Tempering

[0109] The material after low-temperature LSP was heat treated (tempered) at an intermediate temperature of 100°C for 3 hours, and then the sample was taken out of the vacuum heat treatment furnace and air-cooled to room temperature.

[0110] After treatment, the laser-strengthened area was cut in half along the ND direction and the RD direction, and the ND-RD surface was polished and etched to obtain a gradient twin structure as shown in Fig. Figure 7 As shown. Figure 7 It can be seen that compared with the LSP with low temperature treatment, the number of twins is less, and there is no obvious change in the number of twins along the direction of shock wave propagation. The maximum microhardness of the upper surface of the 1-time room temperature LSP is 125.2HV. Under the same stress amplitude (75MPa), the fatigue life of the 1-time room temperature LSP treatment reaches 113362 times, which is slightly lower than the fatigue life of 148691 times of the 3-time low temperature LSP plus tempering treatment.

[0111] Comparative Example 2

[0112] The main difference between this comparative example and Example 1 is that low temperature operation is not performed during the multi-pass laser treatment. The specific steps are as follows:

[0113] (1) Sample pretreatment

[0114] Before LSP, the hot-rolled pure titanium was placed in a vacuum furnace filled with argon and annealed at 800°C for 3 hours to obtain an equiaxed structure and relieve stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0115] (2) LSP processing

[0116] The wavelength is 1064nm and the pulse laser energy is 3.98GW / cm 2 , the pulse duration was 8 ns, and the overlap rate was 50%. Aluminum foil was used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2 mm was added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. A zigzag laser path was used to perform LSP three times, and the laser beam was always kept perpendicular to the sample surface.

[0117] Multi-pass laser treatment without cryogenic treatment: The laser beam is parallel to the ND (normal direction) of the annealed pure titanium, that is, perpendicular to the RD (rolling direction)-TD (transverse direction) surface with an area of ​​2cm×2cm, and laser shock strengthening is performed three times on the same position.

[0118] (3) Tempering

[0119] The material after low-temperature LSP was heat treated (tempered) at an intermediate temperature of 100°C for 3 hours, and then the sample was taken out of the vacuum heat treatment furnace and air-cooled to room temperature.

[0120] After treatment, the laser-strengthened area was cut in half along the ND direction and the RD direction, and the ND-RD surface was polished and etched. Compared with the LSP with low temperature treatment, the number of twins is less, and there is no obvious change in the number of twins along the direction of shock wave propagation. The maximum microhardness of the upper surface of the three-time room temperature LSP is 129.6HV. Under the same stress amplitude (75MPa), the fatigue life of the three-time room temperature LSP treatment reaches 121071 times, which is slightly lower than the fatigue life of 148691 times of the three-time low temperature LSP plus tempering treatment.

[0121] Comparative Example 3

[0122] The main difference between this comparative example and Example 1 is that no tempering treatment is performed, and the specific steps are as follows:

[0123] (1) Sample pretreatment

[0124] Before LSP, the hot-rolled pure titanium was placed in a vacuum furnace filled with argon and annealed at 800°C for 3 hours to obtain an equiaxed structure and relieve stress. Subsequently, the pure Ti was polished with 400# to 2000# sandpaper to reduce the surface roughness.

[0125] (2) LSP processing

[0126] Place the sample fixture in a foam box with liquid nitrogen. Continuously add liquid nitrogen to the foam box so that the liquid nitrogen surface is slightly lower than the sample surface, and transfer heat to the sample to control the temperature at 77 K. After a period of time, when the heat loss and heat supplement of the sample gradually tend to balance, the LSP experiment is immediately carried out in the low temperature treatment.

[0127] The wavelength is 1064nm and the pulse laser energy is 3.98GW / cm 2 , the pulse duration is 8ns, and the overlap rate is 50%. Aluminum foil is used as a sacrificial layer, and a layer of tempered glass with a thickness of about 2mm is added on the aluminum foil as a constraint layer to increase the peak pressure of the laser shock wave. Multiple LSPs are performed using a zigzag laser path, and the laser beam is always kept perpendicular to the sample surface.

[0128] Multi-pass laser treatment of low temperature treatment: The laser beam is parallel to the ND (normal direction) of the annealed pure titanium, that is, perpendicular to the RD (rolling direction)-TD (transverse direction) surface with an area of ​​2cm×2cm, and laser shock strengthening is performed three times on the same position.

[0129] This comparative example does not undergo tempering treatment, and the maximum microhardness of the upper surface of the 3-time low-temperature LSP is 120.8HV. Under the same stress amplitude (75MPa), the fatigue life of the 3-time low-temperature LSP treatment reaches 111975 times. Compared with the 148691 fatigue life of the 3-time low-temperature LSP plus tempering treatment, the fatigue life is slightly reduced.

[0130] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a titanium material with gradient nano-twins, characterized in that: include: The titanium substrate is subjected to annealing treatment, grinding and polishing in sequence to obtain a pretreated substrate; The pretreated substrate is subjected to a multi-pass laser shock strengthening treatment in a low temperature environment of 77K-90K, and then subjected to a tempering treatment.

2. The preparation method according to claim 1, characterized in that: During each laser shock peening process, the laser wavelength is controlled to be 1064nm, the pulse duration is 8ns-15ns, the overlap rate is 50%-80%, and the pulse energy density is 2GW / cm 2 -18GW / cm 2 .

3. The preparation method according to claim 2, characterized in that: During each laser shock peening process, the laser wavelength is controlled to be 1064nm, the pulse duration is 8ns-12ns, the overlap rate is 50%-60%, and the pulse energy density is 3.0GW / cm 2 -6.0GW / cm 2 .

4. The preparation method according to any one of claims 1 to 3, characterized in that During each laser shock peening process, aluminum foil is used as a sacrificial layer, and a constraining layer is provided on the aluminum foil; Preferably, the number of laser shock peening treatments is 2-6 times; Preferably, the aluminum foil is replaced before each laser shock peening treatment.

5. The preparation method according to claim 4, characterized in that: The constraining layer is tempered glass with a thickness of 4mm-6mm.

6. The preparation method according to claim 4, characterized in that: Multiple laser shock peening processes were performed using a zigzag laser path, and the laser beam was kept perpendicular to the sample surface.

7. The preparation method according to claim 1, characterized in that: The pre-treated substrate is placed in liquid nitrogen, and the surface of the liquid nitrogen is lower than the surface of the pre-treated substrate to form the low temperature environment.

8. The preparation method according to claim 1, characterized in that: During the tempering treatment, the treatment temperature is controlled to be 100° C.-200° C., and the treatment time is 2 h-10 h.

9. The preparation method according to claim 1, characterized in that: The annealing treatment is carried out in an inert atmosphere, the annealing temperature is controlled to be 750° C.-850° C., and the annealing time is 2 h-5 h.

10. A titanium material with gradient nanotwins, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.